1998
DOI: 10.1002/(sici)1098-2744(199801)21:1<50::aid-mc7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of p53 loss of function and v-Ha-ras in transformation of mouse keratinocyte cell lines

Abstract: We previously demonstrated that after transduction with the v-Ha-ras oncogene and grafting onto nude mouse hosts, primary epidermal keratinocytes with a null mutation in the p53 gene form tumors with increased growth rates and predisposition to malignant conversion relative to p53 wild-type keratinocytes (Weinberg WC, et al., Cancer Res 54:5584-5592, 1994). To further explore the cooperation between p53 loss of function and activation of the ras oncogene, cell lines were established from the normal epidermises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
16
1
Order By: Relevance
“…PKC, as a survivalpromoting factor, suppresses the activities of various proapoptotic factors, thereby helping cells to escape from p53 surveillance. The elimination of PKC activity releases the ap- Mutation of the p53 gene is a common event in tumorigenesis and often occurs in the late stage of malignancy (5,8,30,48). In various types of cells transformed by oncogenic ras, p53 appears to be mutated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC, as a survivalpromoting factor, suppresses the activities of various proapoptotic factors, thereby helping cells to escape from p53 surveillance. The elimination of PKC activity releases the ap- Mutation of the p53 gene is a common event in tumorigenesis and often occurs in the late stage of malignancy (5,8,30,48). In various types of cells transformed by oncogenic ras, p53 appears to be mutated.…”
Section: Discussionmentioning
confidence: 99%
“…p53, as a transcriptional factor, also regulates the induction and function of several other genes, including Bax and p21, which participate in either p53-dependent apoptosis or growth arrest (28,36,37). It has been observed that mutations in both p53 and ras genes often occur in the same cancer cell (5,8,30,48). In colon cancer cells, Ras mutations have been demonstrated to precede p53 mutations (30).…”
mentioning
confidence: 99%
“…Section 1734 solely to indicate this fact. described previously (10), and these were maintained in medium containing 16% fibroblast conditioned Eagle's minimal essential medium with 8% chelexed serum and 0.05 mM Ca 2ϩ . Primary mouse keratinocytes and cell lines were treated with human recombinant TNF-␣ (R&D Systems, Minneapolis, MN) at final concentrations ranging from 10 to 100 ng/ml for the times detailed.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that p53 is dispensable for normal skin development and differentiation. However, deletion of one or both p53 alleles enhances the establishment of immortal keratinocyte cell lines in vitro (10), suggesting that p53 could participate in keratinocyte mortality in a more subtle way, not involving expression of the major differentiation-related markers. To detect such a contribution of p53 to keratinocyte differentiation or mortality, differential expression of mRNA sequences was examined in keratinocytes isolated from p53 wild-type and null mice and induced to differentiate by Ca 2ϩ in vitro, a condition known to increase p53-dependent transcriptional activity.…”
mentioning
confidence: 99%
“…p53 can also control the senescence of MEFs in a manner that directly restricts the ability of Ras to promote malignant transformation (Serrano et al 1997;Azzoli et al 1998). To examine the participation of E2F7 in this process, we developed multiple shRNAs targeting mouse E2f7 (Supplemental Fig.…”
Section: Cosuppression Of Rb and E2f7 Transforms Primary Mouse Embryomentioning
confidence: 99%